Deutsche Bank Research: Life after covid-19 - Reid, J. (Konzept, 18, 2020)
As our personal, business, social, and economic lives begin to change, this edition of Konzept examines 20 different ways in which the world will be different post covid-19. From working from home, to managing seismic industry change, and eventually paying for the astonishing stimulus measures, many difficult questions must be answered. And given the global health and economic backdrop remains highly uncertain, the way we frame the problems is just as important as the way we address them. It will take years to recover from covid-19. For those who have experienced personal loss, there will be permanent scars. So while societies will eventually heal and economies will recover, the world will be a different place to the one we knew last year. Much change to our personal, business, social, and economic lives awaits. I hope this edition of Konzept goes some way to helping inform us as we take a step into this brave new world. Contents Summaries The investment needed in our healthcare systems The case for inflation The case for deflation How will we pay for all that stimulus? The coming Tech Wall and the covid dilemma Undermining global value chains Climate change: `Acute` threats and unexpected parallels How our flying habits will change Online grocery: fad or fate? An occasion for online banking to capture laggards The stockmarket crash and the detail investors have missed What prior pandemics can teach us today Football: The divide between clubs will grow wider Higher e-duc@tion and the future of homework Our new technology habits Cash is not immune to the virus The end of privacy? The future of work from home The end of creative destruction? How the virus could reduce inequality